Risk factors relating to the early complications of acute myocardial infarction after cardios-intervention treatment - I. A. Golovanova; G. A. Oksak; M. V. Khorosh; M. M. Tovstyak (Сучасні медичні технології)
Purpose of the study. Identify the main risk factors for early complications of acute myocardial infarction after cardiac intervention and assess the prognostic risk.